THE EFFECT OF ASSET STRUCTURE, CAPITAL STRUCTURE, AND MACRO ECONOMICS ON FINANCIAL RISK MANAGEMENT, PROFITABILITY PERFORMANCE, GOING CONCERN AND VALUE OF THE FIRM AND GCG AS MODERATED VARIABLES IN COMPANIES LISTED IN JAKARTA ISLAMIC INDEX - Solichah Solichah; Tri Ratnawti; Srie Hartutie Moehaditoyo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
The population in this study were 30 sharia stock companies listed on the Jakarta Islamic Index in the period 2013 to 2017. The research sample of 16 companies were selected using a purposive sampling method with certain criteria. This type of research is quantitative research, with research data obtained from the IDX website (Indonesia stock exchange) and data testing techniques using PLS test equipment. The results showed that 1) asset structure has no significant effect on financial risk management, 2) asset structure has a significant effect on profitability performance, 3) asset structure has a significant effect on going concern 4) asset structure has a significant effect on the value of the firm 5) capital structure has significant effect on financial risk management 6) capital structure has a significant effect on profitability performance, 7) capital structure has a significant effect on going concern, 8) capital structure has no significant effect on the value of the firm, 9) macroeconomic has a significant effect on financial risk management, 10) Macroeconomic has a significant effect on profitability performance, 11) Macroeconomic has a significant effect on going concern, 12) Macroeconomic has a significant effect on the value of the firm, 13) Financial risk management has a significant effect on the value of the firm, 14) Financial Risk Ma Management has a significant effect on profitability performance, 15) Profitability performance has a significant effect on going concern, 16) Profitability performance has a significant effect on the value of the firm, 17) Going concern has a significant effect on the value of the firm 18) GCG moderates going concern has a significant effect on value of the firm 19) GCG moderates the profitability performance significantly influences the value of the firm 20) GCG moderates the financial risk management does not significantly influence the value of the firm, and at last,21) GCG significantly influences the value of the firm. Keywords: asset structure, capital structure, macroeconomic, financial risk management, profitability performance, going concern, GCG, value of the firm